Baseline adenosine plasma levels indicate differential response to adenosine test and head-up tilt test in syncopal patients. (25th November 2020) - Sotiriadou, M; Antoniadis, A; Vergopoulos, S; Lazaridis, C; Konstantinidis, P; Bakogiannis, C; Virgiliou, C; Gkika, E; Theodoridis, G; Mpalaouri, I; Mpougiouklis, D; Gerou, S; et al.
Abstract: Background/Introduction: Head-up tilt table test (HUTT) and Adenosine test (ADT) can be useful in the diagnostic evaluation of syncope. Adenosine plasma (ADP) and Adenosine receptor (ADR) levels may differentiate the outcomes of HUTT and ADT but their precise role in the risk stratification of patients with syncope remains elusive. Purpose: We sought to assess the ADP and ADR levels in patients without structural heart disease who underwent HUTT and ADT tests as part of the diagnostic workup of syncope. We specifically investigated differences in the outcomes of the HUTT and ADT tests as well as to the ADP levels during HUTT according to the baseline ADP levels. Methods: HUTT and ADT were performed as per the standard protocols. ADT was considered positive in the event of asystole >6 seconds or heart block for >10 seconds after intravenous Adenosine 0.15 mg/kg administration in the supine position. ADP levels (ppm/Um/L) were assessed at three timepoints during the HUTT: at baseline (supine), immediately after bed tilt and, in cases of a positive HUTT, at the time of syncope. Patients were categorized in terciles of low, intermediate and high baseline ADP levels. We also assessed the A2A ADR levels of monocytes. Results: We prospectively analyzed 106 patients (62 women, age 46.87±20.63 years). ADT was positive in 14.2% of patients and HUTT in 47.2% of patients. Females were more likely to have low ADP levels (odds ratio [OR] 2.70, 95% Confidence Interval [CI] 1.04 to 6.94, p<0.05). Patients with low baseline ADP levels showed a trend for positive ADT (OR 3.15, 95% CI 1.05 to 10.85, p=0.07), while patients with high baseline ADP levels showed a trend for negative HUTT (OR 2.35, 95% CI 0.94 to 5.90, p=0.075). Within patients with positive HUTT, those with low baseline ADP levels, showed an increase in ADP in the tilt phase (0.063 vs 0.027 ppm/Um/L, p<0.05) but not at the time of syncope (0.045 ppm/Um/L) while those with intermediate baseline ADP levels showed an increase in ADP in the tilt phase (0.16 vs 0.095 ppm/Um/L, p<0.05) which persisted during syncope (0.18 ppm/Um/L, p<0.05). Patients with high baseline ADP levels did not exhibit differences in ADP during positive HUTT. Higher baseline ADP levels were associated with smaller increases in the tilt phase (Pearson's r −0.621, p<0.001). ADR levels in patients with positive HUTT correlated positively with baseline ADP levels (Pearson's r 0.878, p<0.001). Conclusion(s): Baseline ADP levels may be related to the outcome of ADT and HUTT. ADP increases during HUTT except for patients with high baseline ADP. ADP and ADR levels warrant further investigation as they may characterize a subset of patients with specific responses to HUTT and may be implicated in the pathophysiology of reflex syncope. Funding Acknowledgement: Type of funding source: None